Murwakala in Mass Ruwatan Ceremony in Surakarta: Its Relevance and Meaning in a Modern Perspective - Sukandar, Rudi; Ramonita, Latifa; Harti, Sri (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
The Ruwatan tradition in Javanese culture involves a sacred performing art called Murwakala. This performance is carried out individually or collectively to self-purify, ask for forgiveness, or ward off disaster for individuals of various ages and social classes. Individuals categorized as Sukerta (bring bad luck, are dirty, or have disturbances) are considered not yet pure and, therefore, require a ruwatan (purification) ritual. Given the intensive use of symbols in the ruwatan ritual, understanding the messages conveyed through the performance art and ritual becomes problematic. This study aims to investigate how modern audiences interpret the ruwatan ritual. Using the theory of Symbolic Interaction, this study adopts a qualitative method. Data collection is done through observation, document studies, and in-depth interviews. Informants are the ruwat puppeteer, ruwat participants, and audiences. The findings of this research demonstrate that for the mass ruwatan tradition and Murwakala performance to maintain their relevance and significance in contemporary society, the symbolic meanings embedded within these practices must be conveyed more explicitly to both participants and the broader public. Ruwatan participants give meaning to ritual symbols and actions according to their cultural background, religion, and personal experience as an interpretation of the performance given by the ruwat puppeteer. Moreover, the study highlights the necessity of communicative innovation, such as implementing informational media, to support the continued vitality and relevance of ruwatan rituals in modernity.